Gestión del Marketing para el posicionamiento de la empresa Ferretería y Maderas Kattya en el cantón Pujilí - Singaucho Espin, Katya Lisbeth (2022)
Marketing is important because it helps to consolidate the relationship between client and company, for which this study proposes to diagnose Marketing Management for the positioning of the company Ferretería y Maderas Kattya in the Pujilí canton, in order to solve the problem of ignorance of the hardware store by the public, in addition to this the increase in similar ventures has made customers move in the market. For this, the qualitative methodology with a deductive descriptive approach was used. Through semi-structured surveys with 21 questions for potential customers, 14 questions for current customers and 16 questions for internal customers, in addition to 1 interview with the company manager, where the main results were that: the hardware store is not positioned, in addition to the fact that the client frequents a place with similar characteristics due to its prices, location and product variety. Which contributes significantly to the positioning study of the company to identify the internal and external situation, so that strategies were carried out that help to achieve a sustainable positioning in the market, in addition to this, the financial feasibility of the positioning plan was seen. through the return on investment indicator.